Chuva de sementes em um fragmento de floresta estracional semidecidual secundária no sul do estado de Minas Gerais - Silva, Fábio Francisco Da (2013)
The seed rain is the key element in the dynamics of the forest populations, because it has the paper of forming the bank of seeds and seedlings, that represent the initial phase of the space organization of new plants, influencing in the vegetable communities' structure, besides in degraded areas and promoting the new individuals' entrance in the community. This study aimed to demonstrate which species were more abundant and determine the period they were more frequent, in which stations and in which location of the fragment. 100 collectors of 0,25 m2 were placed (50 X 50 cm), with height of 10 cm, made in wood, telados with mesh of polyethylene of 1 mm. These aleatoriamente were distributed inside of ten portions of 200 m2 (10 X 20 m) which were subdivided in 50 subparcelas of 4 m2 of the which 10 were raffled for us to receive the seed collectors. Five of those portions were marked in the border of the fragment and five inside the studied fragment. The collections were accomplished every two months during one year. For the significant variation sources (N >200) the test was applied Scott-Knott to 5% of significância and contrast non ortogonal among the rain stations and of drought, following the test Scheffé, also to 5% of significância. It was also evaluated if there was difference between the interior and the border of the fragment in each collection. There was significant difference in relationship the interior and the border of the fragment, and the border presented the largest rate of dispersion of seeds, in the first collection it was observed the largest amount of dispersed propágulos and P. vellosiana the species that had larger dispersion in the fragment was, mainly in the first collection. Eleven species were considered significant and the different analyses were accomplished mentioned previously. Those results suggest that few species contributed in the forest dynamics, that the border was favored in relation to the interior of the fragment. The distribution of the species was linked your characteristics fenologics and the climatic stations during the collections.